Product-Focused Software Process Improvement : 20th International Conference, PROFES 2019, Barcelona, Spain, November 27-29, 2019, Proceedings /: 20th International Conference, PROFES 2019, Barcelona, Spain, November 27-29, 2019, Proceedings. (2019) - Unknown
No abstract available